Periodontal Pathogens Methods and Protocols - Nagano, Keiji; Hasegawa, Yoshiaki; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Humana, 2021)
This book addresses the major periodontal pathogens implicated as causal agents in periodontal disease, including Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, Fusobacterium nucleatum, Aggregatibacter actinomycetemcomitans, and Prevotella spp. Beginning with methods for bacterial genetic manipulation, the volume continues with sections on experimental methods to examine virulence factors, interactions with other pathogenic microorganism and host cells, as well as a chapter on an animal model of periodontitis. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Periodontal Pathogens: Methods and Protocols serves as an extensive and useful reference for researchers studying periodontal pathogens and will help elucidate the causes of periodontal disease and the systemic diseases related to it.
Site-Directed and Random Mutagenesis in Porphyromonas gingivalis: Construction of Fimbriae-Related-Gene Mutant -- Genetic Manipulations of Oral Spirochete Treponema denticola -- Construction of a Gene-Deletion Mutant in Tannerella forsythia -- Construction of a Mutant in Prevotella melaninogenica Using the Conjugation Transfer Method with Escherichia coli -- Genetic Transformation of Fusobacterium nucleatum -- Genotyping of Porphyromonas gingivalis in Relationship to Virulence -- Transport and Polymerization of Porphyromonas gingivalis Type V Pili -- Purification of Native Mfa1 Fimbriae from Porphyromonas gingivalis -- Crystallization of Recombinant Fimbrial Proteins of Porphyromonas gingivalis -- Enzymatic Characteristics and Activities of Gingipains from Porphyromonas gingivalis -- Structural Characterization of the Type IX Secretion System in Porphyromonas gingivalis -- Methods for Functional Characterization of the Type IX Secretion System of Porphyromonas gingivalis -- Purification of Tannerella forsythia Surface (S-) Layer Proteins -- Separation of Glycosylated OmpA-Like Proteins from Porphyromonas gingivalis and Tannerella forsythia -- Intranasal Vaccine Study Using Porphyromonas gingivalis Membrane Vesicles: Isolation Method and Application to a Mouse Model -- Analysis of the Butyrate-Producing Pathway in Porphyromonas gingivalis -- Characterization of the Treponema denticola Virulence Factor Dentilisin -- Evaluation of the Virulence of Aggregatibacter actinomycetemcomitans through the Analysis of Leukotoxin -- Lipoprotein Extraction from Microbial Membrane and Lipoprotein/Lipopeptide Transfection into Mammalian Cells -- Analysis of the Interaction between HIV and Periodontopathic Bacteria that Reactivates HIV Replication in Latently Infected Cells -- Invasion of Gingival Epithelial Cells by Porphyromonas gingivalis -- Analysis of Interaction between Porphyromonas gingivalis and Endothelial Cells In Vitro -- Analysis of Experimental Ligature-Induced Periodontitis Model in Mice.
Keywords: Microbiology; Dentistry; Medicine; Microbiology; Dentistry; Biomedicine, general